The Distortionary Effects of Government Procurement: Evidence from Medicaid Prescription Drug Purchasing - Duggan, Mark; Scott Morton, Fiona M. (Quarterly Journal of Economics, 2006)
In 2003 the federal-state Medicaid program provided prescription drug coverage to more than 50 million people. To determine the price that it will pay for each drug, Medicaid uses the average private sector price. When Medicaid is a large part of the demand for a drug, this creates an incentive for its maker to increase prices for other health care consumers. Using drug utilization and expenditure data for the top 200 drugs in 1997 and in 2002, we investigate the relationship between the Medicaid market share (MMS) and the average price of a prescription. Our estimates imply that a 10-percentage-point increase in the MMS is associated with a 7 to 10 percent increase in the average price of a prescription. In addition, the Medicaid rules increase a firm's incentive to introduce new versions of a drug in order to raise price. We find empirical evidence that firms producing newer drugs with larger sales to Medicaid are more likely to introduce new versions. Taken together, our findings suggest that government procurement rules can alter equilibrium price and product proliferation in the private sector.